Sastra Cyber: Alternatif Komunikasi antara Karya Sastra dan Masyarakat Pembaca - Hidayat, Arif (Fakultas Dakwah IAIN Purwokerto, 2008)
The existence of cyberliterary is an impact of technology development. Cyberliterary become new alternativefor writer to communicate his works to people. From Indonesian literary domain, we can conclude that a writer capabilitydetermined by his work